2019
DOI: 10.5194/hess-23-2015-2019
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of three decades of hydrological research at Scotty Creek, NWT, Canada

Abstract: Abstract. Scotty Creek, Northwest Territories (NWT), Canada, has been the focus of hydrological research for nearly three decades. Over this period, field and modelling studies have generated new insights into the thermal and physical mechanisms governing the flux and storage of water in the wetland-dominated regions of discontinuous permafrost that characterises much of the Canadian and circumpolar subarctic. Research at Scotty Creek has coincided with a period of unprecedented climate warming, permafrost tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 95 publications
(147 reference statements)
0
52
0
Order By: Relevance
“…The small annual loss of permafrost in a 10‐year simulation indicates that the current condition of peat plateaux results in permafrost degradation. Given long enough periods forced with these consistent boundary conditions, it is expected that the permafrost will begin to degrade, as discussed for this field site in Quinton et al (). This is analogous to results found by Briggs et al () who show that though permafrost aggradation has been observed in draining lakes, this phenomenon is only transitionary as the permafrost is an artifact of the groundwater regime and shading from shrubs, and it is expected to thaw within the decade.…”
Section: Synthesismentioning
confidence: 89%
“…The small annual loss of permafrost in a 10‐year simulation indicates that the current condition of peat plateaux results in permafrost degradation. Given long enough periods forced with these consistent boundary conditions, it is expected that the permafrost will begin to degrade, as discussed for this field site in Quinton et al (). This is analogous to results found by Briggs et al () who show that though permafrost aggradation has been observed in draining lakes, this phenomenon is only transitionary as the permafrost is an artifact of the groundwater regime and shading from shrubs, and it is expected to thaw within the decade.…”
Section: Synthesismentioning
confidence: 89%
“…Intensive field studies first began at Scotty Creek in the 1990s with the goal of better understanding northern peatland landscapes (Quinton et al 2019). A comprehensive archive of ground-based energy and water measurements was used in this study to examine the temporal variation in landscape characteristics at Scotty Creek.…”
Section: Field-based Methodsmentioning
confidence: 99%
“…The Scotty Creek Research Station (SCRS; 61.3°N, 121.3°W) has been the site of extensive field-based studies over the past 20 years and provides an opportunity to use long-term 160 and detailed datasets that are uncommon in northern research (Quinton et al 2019). The trajectory of change proposed in this study is based upon observational data collected by the SCRS and geospatial data across the broader study region.…”
Section: Scotty Creek Nwtmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost and logistical challenges of working in remote and northern areas are rarely explicitly mentioned in publications (e.g., Petrone, Jones, Hinzman, & Boone, ; Shatilla & Carey, ). However, these factors cause research resources to be funnelled into a handful of long‐term monitoring sites with existing support (e.g., Scotty Creek, Quinton et al, ; Baker Creek, Spence & Hedstrom, ; Wolf Creek, Rasouli, Pomeroy, Janowicz, Williams, & Carey, ; Utikuma Region Study Area, Devito, Mendoza, & Qualizza, ). These observatories are extremely valuable, as they provide long‐term high spatial and temporal resolution datasets that improve process understanding and predictive modelling, and are essential in identifying hydrological trends (e.g., DeBeer et al, ; Rasouli, Hernández‐Henríquez, & Déry, ; Spence, Kokelj, Kokelj, McCluskie, & Hedstrom, ; Tetzlaff, Carey, McNamara, Laudon, & Soulsby, ).…”
Section: Making the Most Of The Available Datamentioning
confidence: 99%